Effects of Gut Bacteria Depletion and High‐Na+ and Low‐K+ Intake on Circulating Levels of Biogenic Amines. Issue 4 (12th December 2018) - Blaženović, Ivana; Oh, Young Taek; Li, Fan; Ji, Jian; Nguyen, Ahn‐Khoi; Wancewicz, Benjamin; Bender, Jeffrey M; Fiehn, Oliver; Youn, Jang H.
Abstract : Scope: High‐sodium and low‐potassium (HNaLK) content in Western diets increases the risk of hypertension and cardiovascular disease (CVD). It is investigated if the dietary minerals interact with gut bacteria to modulate circulating levels of biogenic amines, which are implicated in various pathologies, including hypertension and CVD. Methods and results: Using a metabolomic approach to target biogenic amines, the effects of gut bacteria depletion and HNaLK intake on circulating levels of biogenic amines in rats are examined. Forty‐five metabolites whose plasma levels are significantly altered by gut bacteria depletion ( p < 0.05) are found, indicating their regulation by gut bacteria. Many of them are not previously linked to gut bacteria; therefore, these data provide novel insights into physiological or pathological roles of gut bacteria. A number of plasma metabolites that are altered both by gut bacteria and HNaLK intake are also found, suggesting possible interactions of the diet and gut bacteria in the modulation of these metabolites. The diet effects are observed with significant changes in the gut bacterial taxa Porphyromonadaceae and Prevotellaceae ( p < 0.05). Conclusion: The dietary minerals may regulate abundances of certain gut bacteria to alter circulating levels of biogenic amines, which may be linked to host physiology or pathology. Abstract : High‐sodium and low‐potassium (HNaLK) content in Western diets increases the risk of hypertension and cardiovascular disease (CVD) . Using metabolomic and metagenomic approaches, the effects of HNaLK intake and gut‐bacteria depletion on circulating biogenic amines are examined in rats. The data suggest the dietary minerals interact with gut bacteria to modulate circulating biogenic amines, which may contribute to hypertension and CVD.